A Comprehensive Review on the Impact of Teacher Feedback in Language Development for ESL/EFL Learners - Hossain, Kazi Imran; Ahmed, Md Kawser; Mahmud , Md Sabid (IUBAT Review, 2024)
This comprehensive review investigates the multifaceted impact of teacher feedback on English as a Second/Foreign Language (ESL/EFL) learners' language development. The paper examines feedback modalities, including written, verbal, and technological approaches, and recommends a multimodal strategy to accommodate diverse learner preferences. The challenges in providing feedback, such as balancing corrective and affirming feedback and individualising responses in large classes, are discussed. Future recommendations include using technology to provide scalable and personalised feedback, encouraging learner agency through self-assessment, and prioritising cultural responsiveness. The integration of socio-emotional dimensions into feedback practices is highlighted, emphasising the importance of a comprehensive approach to ESL/EFL language development. Ongoing collaboration among teachers, students, and researchers is recognised as critical for shaping evidence-based practices and advancing inclusive and effective ESL/EFL teaching. This paper offers valuable insights for teachers, researchers, and policymakers looking to improve language development strategies in a variety of ESL/EFL contexts. IUBAT Review—A Multidisciplinary Academic Journal, 7(1): 218-229